Mais médicos project and hospitalizations for conditions sensitive to primary care in a health district of Salvador - Moreno Neto, José Luiz (2022)
Primary Health Care concerns itself with shifting the care model by employing the Family Health Strategy. One obstacle to this resolution is the lack of doctors in the most vulnerable regions. To attract these professionals, hiring policies have been instituted. One indicator of Primary Health Care quality is the proportion of hospitalizations for conditions sensitive to Primary Care. Given this context, this study describes the time trend of hospitalizations for conditions sensitive to Primary Care in a health district of Salvador, Bahia, Brazil, before and during the implementation of the Mais Médicos Project. Data were collected from the Hospital Information System and the National Registry of Health Establishments for the district, between 2010 and 2016. Proportion of physicians by the provision programs and the proportion of hospitalizations for conditions sensitive to Primary Care was calculated in general and for the 20 major groups. Results showed that hospitalizations for conditions sensitive to Primary Care ranged from 21.8% of total hospital admissions in 2010 to 8.2% in 2016, decreasing after implementation of the provision programs. These findings suggest that the provision programs influenced the reduction of hospitalizations for sensitive conditions to Primary Care, pointing to the need for further studies to prove this hypothesis.